Pilihan Kata dan Konstruksi Perempuan Sunda dalam Majalah Manglè: Kajian Linguistik Korpus Diakronik - Yuliawati, Susi; Hidayat, Rahayu Surtiati; Rahyono, F X; Kwary, Deny A (Paradigma: Jurnal Kajian Budaya, 2017)
Gender identity, one of the most important social categories in people’s lives, is socially constructed, and language is claimed to have a significant role in constructing the gender identity. This paper studies the construction of Sundanese women through five Sundanese nouns referring to women found in the corpus of Manglè magazine, published between 1958–2013. The research employs a mixed-method design in which quantitative analysis is combined with qualitative analysis to investigate how the nouns referring to women are used to construct Sundanese women from the periods of Guided Democracy (1958–1965) to Reform Era (2004–2013). The quantitative analysis is used to examine the frequency of word occurrence diachronically. The frequency of word occurrence is subsequently interpreted qualitatively by considering social and cultural contexts, such as the norms of speech levels in Sundanese, Sundanese belief about marriage, and gender issues. The result of analysis shows that women are constructed in various identities by every noun referring to them. The lexical choices used to construct women are greatly influenced by the social and cultural contexts.